Cathode flow velocity and pressure gradient oscillations in impedance spectroscopy of PEM fuel cells - Andrei Kulikovsky (Journal of Power Sources Advances)
In electrochemical impedance spectroscopy experiments with PEM fuel cells, the applied AC current induces oscillations of the mass flow across the gas diffusion layer/cathode channel interface. These oscillations perturb the air flow velocity and pressure in the cathode channel. By analogy with Berman’s approach, the transient Navier–Stokes equations for air flow in a channel with a permeable wall are reduced to a single equation for the transverse profile of the streamwise flow velocity (SFV). Linearization and Fourier-transformation of this equation leads to an ODE for the SFV perturbation amplitude. The numerical solution shows that harmonic perturbation of the cell current density generates oscillations of the pressure gradient and SFV. As the frequency increases, the transverse shape of the SFV oscillations amplitude flattens in the main body of the flow, while the peaks form at the channel walls. Averaged across the channel amplitudes of pressure gradient and SFV oscillations linearly increase along the channel. Analytical formulas for incorporation of these effects into impedance models for PEM fuel/electrolysis cell are derived.